Recent Trends in the Study of Springs in Nepal: A Review (Bulletin of the Department of Geology, 2024)
Springs, a component of groundwater systems, are a vital source of fresh water for fulfilling people's demand for drinking water, household uses, and irrigation, especially in the Middle Hill region of Nepal. Springs provide water for base flows and lifelines for many rivers originating from the Middle Hill regions. The present study reviews a recent trend of spring studies and investigations in Nepal through a systematic search of published and unpublished works related to springs, which are freely available. The results show 47 publications, out of 30 are published, and 17 are unpublished. The origin of published work is mainly related to project-related works, whereas unpublished works come from the academic sector for fulfilling academic criteria for thesis research. According to the physiographical division of Nepal, the study area falls in the Middle Hills of Nepal, with the maximum area located in Bagmati Province. Most of the studies that qualitative rather than quantitative information of springs. Studies are not linked with spring source and their seasonal dynamics. However, clearly available data, attributes and information about springs from 47 reviewed documents are noted. Systematic data generation and a standard framework for data collection are also missing. Nevertheless, out of 47 studies, including 11 published and 4 unpublished, the total number of springs per sq. km. in the Middle Hill region of Nepal is estimated as 2.57, which can be integrated after more research on future springs–related work.